CONFLICT AND INTEGRATION IN THE 2024 MAKASSAR CITY REGIONAL HEAD GENERAL ELECTION - Arief Rahman Hakim; Heri Tahir; Mustari Mustari; Hasruddin Nur; Najamuddin Najamuddin; Romansyah Sahabuddin (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
This study examines conflict and social integration in the 2024 Regional Head Election (Pilkada) of Makassar City. Elections in democratic societies function not only as mechanisms for leadership recruitment but also as arenas that potentially generate social conflict while simultaneously opening opportunities for social integration. This research aims to identify empirical factors that trigger conflict, analyze factors that encourage integration, and describe the role of conflict resolution institutions particularly the Election Organizers Honorary Council (DKPP) in managing post-election disputes. The study employs a qualitative descriptive approach with data collected through in-depth interviews, observation, and documentation. Informants consisted of election organizers (KPU and Bawaslu), law enforcement officers within Gakkumdu, academics, and political observers. Data were analyzed through data condensation, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings reveal that conflict during the Makassar Pilkada was driven by sociological factors such as emotional attachment to candidates, dissatisfaction with vote-counting results, and social segregation among supporters, as well as institutional factors including perceptions of organizer neutrality, electoral violations, and internal party disputes. Conversely, social integration emerged through acceptance of election results, effective voter participation, security stability, post-election collaboration, and public trust in electoral institutions. The study concludes that the effective functioning of social and electoral institutions plays a crucial role in transforming electoral conflict into social integration, thereby maintaining democratic stability at the local level.